Marching on a Long Road:A Review of the Effectiveness of the Mother-Tongue Education Policy in Post-Colonial Hong Kong - Li, Vickie W. L.; Majhanovich, Suzanne (GIST – Education and Learning Research Journal, 2010)
This paper reports a study of the effectiveness of the mandatory mother-tongue education policy in post-colonial Hong Kong. Special attention has been placed on students’ academic achievement before and after the policy implementation in 1998 in order to find out if students learn better through their mother tongue without sacrificing their knowledge of the English language. A content analysis has been conducted on the relevant policy documents, and students’ public examination results have been gathered to serve as a policy effectiveness indicator. Findings reveal that mother-tongue education is beneficial to students’ learning in some subjects, especially the language-intensive ones. However, students’ performance in English learning has been adversely affected by the policy. We end with suggestions in response to the recently announced finetuning arrangements of the mother-tongue education policy.